Penerapan Sistem Informasi Manajemen Daerah (SIMDA) - Syafri Dharma; Raden Biroumb; Holten Sion (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to describe and analyze the application of SIMDA at the Sukamara Regency Public Housing and Settlement Area Service. Qualitative research approach methods always start from social phenomena captured by researchers. This research was conducted within the Sukamara Regency Public Housing and Settlement Area Service. Data analysis techniques in the field in this research were carried out using the Miles and Huberman model. The research results show that in terms of input, process, and output it is as expected, namely timely planning and accrual-based SAP implementation, but SIMDA does not make financial planning and reporting more transparent. Conclusion, as expected, namely timely planning and accrual-based SAP implementation, SIMDA does not make financial planning and reporting more transparent. Keywords: Government Governance, Information Systems.